Strengthening the connection between acquired brain injury (ABI) and family violence: the importance of ongoing monitoring, research and inclusive terminology - Lansdell, Gaye T. (Journal of family violence, 2022)
Family violence (FV) harms communities worldwide so FV prevention strategies and effective responses are urgently needed. This article reports on FV apparent in a study which explored the experiences of people with both ABI and justice system encounters in Victoria, Australia. One hundred interviews and one focus group consulted people with ABI, their families and carers, and various stakeholder groups in the Victorian justice system in Australia. Qualitative content analysis determined dominant themes and sub-themes and the less common themes. Inductive interpretive content analysis identified themes commonly found in previous published research and themes that appeared unique to, or unanticipated in, our data, such as the FV theme upon which this article focuses. Our findings reveal that FV has adversely affected many people with ABI who came into contact with Victoria’s justice system. Further, as ABI and FV often co-occur with substance abuse, mental health problems, socio-economic and many other significant disadvantages, for some FV perpetrators with an ABI, their ABI symptoms and characteristic co-morbidities may be a mitigating factor in their offending. The connection between ABI and family violence emerged as a troubling research theme. Indeed, the impact of FV on too many of our participants with an ABI compels us to call for further related research and secondary prevention programs targeted at FV victims, and offenders, living with ABI. An intersectional understanding of family violence and TBI/ABI in social ecological contexts is required to better understand brain injury at both individual and population levels.